Profesionalisme Pendampingan Proyek P5 pada Siswa Berkebutuhan Khusus: Studi Kemandirian Guru di SMAN 1 Gedangan Sidoarjo - Roudhoh Binuchillah; Aulya Ridwan (Lembaga Yasin AlSys, 2026)
The Proyek Penguatan Profil Pelajar Pancasila (P5) within the Kurikulum Merdeka is integrated to develop students who are competent, of strong character, and behave in accordance with Pancasila values, including students with special needs in inclusive education settings. In practice, regular teachers are required to provide equivalent support to all students, even though some do not have competencies as special assistant teachers (GPK) or a specific background related to P5 projects. Although previous studies have extensively discussed the implementation of P5 and learning support for children with special needs, there remains a limited number of studies examining the role of regular teachers as learning companions in P5 activities for all students, including those with special needs. This study aimed to analyze the professionalism of P5 project assistance for students with special needs, with a focus on the independence of regular teachers in managing inclusive classes at SMAN 1 Gedangan Sidoarjo. The research employed a qualitative method with a field study at SMAN 1 Gedangan Sidoarjo, collecting data through interviews with several informants, field observations, and an in-depth literature review. The findings indicate that the planning process prior to P5 implementation is arranged through collaborative meetings between regular teachers and GPK teachers, enabling regular teachers to independently apply assistance strategies that are aligned with the P5 activity flow in the school. This study affirms that regular teachers play a crucial role in providing inclusive and professional P5 assistance for students with special needs, with implications for strengthening teacher training, optimizing collaboration with special assistant teachers, and developing flexible P5 strategies that are more responsive to student needs in inclusive classrooms.